2006
DOI: 10.1007/s10661-006-9341-3
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants-Induced Oxidative Damage on the Carp Cyprinus carpio Collected from the Upper Yellow River, China

Abstract: The Yellow River, the second largest river in China, is the most important resource of water supply in North China. In the last 40 years, even in the upper Yellow River, with the development of industry and agriculture, more and more contaminants have been discharged into this river and greatly polluted the water. Although a routine chemical component analysis has been performed, little is known about the real toxic effects of the polluted water on organisms at environmental level. To explore whether the pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 33 publications
5
21
0
1
Order By: Relevance
“…This may be due to an increase in hydrogen peroxide production acting as signal to activate CAT in order to transform this highly toxic radical to less toxic compounds. A similar response has been obtained in other aquatic organisms exposed to other contaminants such as metals and pesticides (Huang et al 2007). However, it is worth noting that excess production of peroxide not only activates CAT, but also favors NSAID oxidation and production of reactive metabolites, potentially affecting other biomolecules (Galati et al 2002;Huq 2006).…”
Section: Antioxidant Activitysupporting
confidence: 75%
“…This may be due to an increase in hydrogen peroxide production acting as signal to activate CAT in order to transform this highly toxic radical to less toxic compounds. A similar response has been obtained in other aquatic organisms exposed to other contaminants such as metals and pesticides (Huang et al 2007). However, it is worth noting that excess production of peroxide not only activates CAT, but also favors NSAID oxidation and production of reactive metabolites, potentially affecting other biomolecules (Galati et al 2002;Huq 2006).…”
Section: Antioxidant Activitysupporting
confidence: 75%
“…But LPO intensity assessed as TBARS level did not differ between two sites. Similar results were obtained by Huang et al (2007) in the hepatopancreas of carp from polluted site, unlike the responses of other studied tissues, kidney and intestine. Despite differences in the activities of superoxide dismutase (SOD), glutathione transferase (GST) and glutathione peroxidase (GPx), the level of LPO was the same in the fish from two sites, indicating a stronger antioxidant capacity of this organ.…”
Section: Oxidative Manifestations: Reactive Oxygen Species Damage Tosupporting
confidence: 86%
“…The depletion of catalase activity or its stability along with increment of SOD activity were reported (Pandey et al, 2003;Stanic et al, 2006;Huang et al, 2007), and even although catalase mRNA levels were higher in the exposed fish (Hansen et al, 2006a). Dorval and colleagues (2005) in hepatic and adrenal tissues of white sucker (C. commersoni) from a river Yamaska that drains an agricultural region in Québec (Canada) found that in fish from the contaminated sites catalase and GPx activities were lower than those in the fish from reference site.…”
Section: Antioxidant Enzymesmentioning
confidence: 97%
See 1 more Smart Citation
“…The significant increase in the SOD activity may indicate an increased production of superoxide anions and H 2 O 2 in zebrafish. In general, these powerful and potentially harmful oxidizing agents could be metabolized by CAT and GPx into harmless agents, including H 2 O and O 2 (Huang et al, 2007). However, the GPx and CAT activities were significantly inhibited in this study, which may reflect a damaged defense chain caused by the DCAcAm.…”
Section: The Metabolism Damage Of Dcacammentioning
confidence: 56%